Hibernating myocardium: morphological correlates of inotropic stimulation and glucose uptake. Issue 4 (1st April 2000) - Pagano, D; Townend, J N; Parums, D V; Bonser, R S; Camici, P G
Abstract : BACKGROUND: In patients with postischaemic left ventricular dysfunction, segments recovering function after revascularisation (hibernating myocardium) may not respond during dobutamine echocardiography, despite preserved [ 18 F] 2-fluoro-2-deoxy-D-glucose (FDG) uptake at positron emission tomography. OBJECTIVE: To investigate whether this lack of response might reflect the degree of ultrastructural change in hibernating myocardium. METHODS: Transmural biopsies were obtained from 22 dysfunctional segments in 22 patients during coronary artery bypass grafting and examined by light and electron microscopy. Wall motion scores and coronary vasodilator reserve were assessed before and after coronary artery bypass grafting (CABG). RESULTS: Mean (SD) wall motion score improved in all segments following CABG (from 2.24 (0.4) to 1.55 (0.4); p < 0.0001), confirming hibernating myocardium. In these segments myocardial blood flow (positron emission tomography with H2 15 O) before CABG was similar to that in normal volunteers (1.02 (0.24) v 1.02 (0.23) ml/min/g), while the coronary vasodilator reserve was blunted (1.26 (0.7) v 3.2 (1.6); p < 0.0001). Myocardial blood flow was unchanged after CABG, whereas coronary vasodilator reserve increased to 2.10 (0.90) (p < 0.0007). In hibernating myocardium myofibrillar loss, interstitial fibrosis, and glycogen-rich myocytes were more marked than in control donor hearts. On the basis of the response to dobutamine before CABG, two functional groups were identified: group A, segments with inotropic reserve (n = 15); group B, segments without inotropic reserve (n = 7). FDG uptake was similar in group A and group B (0.40 (0.1) v 0.44 (0.1) μmol/min/g). In group B there was more myofibrillar loss (26 (8)% v 11 (5)%; p = 0.0009) and glycogen-rich myocytes (28 (11)% v 17 (10)%; p = 0.02), whereas interstitial fibrosis, myocardial blood flow, and coronary vasodilator reserve were similar in the two groups. Myofibrillar loss was the only independent predictor of inotropic reserve (p = 0.01). CONCLUSIONS: Hibernating myocardium is characterised by a reduced coronary vasodilator reserve which improves on revascularisation and shows a spectrum of ultrastructural changes that influence the response to dobutamine, while FDG uptake is invariably preserved.